Impact of Nitrogen and Phosphorus on the Growth, Yield and Quality of Maize (Zea Mays L.) Fodder in Pakistan (2013)
Balanced nutrition is a prerequisite for getting higher field of fodder. The present investigation determined the effect of nitrogen (N) and phosphorus (P) combinations on the fodder yield, growth and quality of maize (Zea mays L.) at the Agronomic Research area, University of Agriculture, Faisalabad Pakistan during 2006, spring. The experiment was laid out in RCBD with three replicates with net plot size of 92.2m2. The maize cultivar Golden-1 was fertilized with N and P at the rates of 0-0 (control), 100-50, 100-75, 100-100, 150-50, 150-75, 150-100, 200-50, 200-75 and 200-100 kg ha-1 . Plant height , number of leaves per plant, stem diameter and leaf area per plant were influenced significantly by the N and P different treatments over control. Highest green fodder yield (67.84 t ha-1) was obtained by applying N and P at the rate of 150 kg N ha-1 and 100 kg P ha-1. Crude protein (10.4%), crude fiber (34.9%) and total ash (11.5%) were highest at 200-100 kg NP ha-1. based on these findings, better maize fodder quality could be obtained through application of 200-100 kg NP ha-1 while for achieving higher fodder yield could be attained with application of 150-100 kg NP ha-1. Other maize cultivars including hybrids in Pakistan should be evaluated under different edaphic and agro-climatic normals.